(untitled) (Bangladesh Journal of Medical Microbiology, 2013)
This study was designed for early detection of drug resistance in Category II failure tuberculosis (TB) patients and to introduce a simple method to detect multi-drug resistant Mycobacterium tuberculosis (M.TB) from direct sputum sample. Total one hundred Ziehl-Neelsen (Z-N) staining positive Category II failure TB patients were enrolled in this study. Culture and drug susceptibility was done by slide and conventional method, among which 90 samples were positive by slide culture and 87 samples were positive by conventional culture. Susceptibility test by slide method showed 85 (94.44%) resistance to one or more anti -TB drugs. Resistance to Isoniazide (INH), Rifampicin (RMP), Ofloxacin (OFX) and Kanamycin (KA) was 94.44%, 84.44%, 31.11% and 4.44% respectively. By this method 80% isolates were detected as Multi-drug resistant (MDR) M.TB and 4.44% isolates were detected as Extended drug resistant (XDR) M.TB. Susceptibility results by slide DST demonstrated good concordance with conventional DST methods. Statistical analysis showed that, Sensitivity of slide DST method was 98.8%. Susceptibility results were available much faster by slide DST method (12.5±0.5 days) compared to that by conventional DST (60.4±5.9 days). Rate of contamination was also much lower by slide DST method than conventional culture (0.18% Vs 3.25%). The present study reflected that the slide DST method could be applied as rapid diagnostic tool to detect drug resistance among Category II failure TB cases, which is essential for applying appropriate therapy. DOI: http://dx.doi.org/10.3329/bjmm.v5i2.16910 Bangladesh J Med Microbiol 2011; 05 (02): 6-10